Caracterização mineralógica e química dos regolitos de uma área de transição savana-floresta em Roraima: uma análise da evolução da paisagem - MENESES, Maria Ecilene Nunes da Silva (2015)
The present study was carried out in an area of transition savanna-forest of the north of Roraima state. The main objective was to characterize the landscape regoliths and evaluate the evolution of the landscape during the late Holocene and even the present-day. Thus, four topossequences representative of the geomorphological, pedological and botanical patterns along the regional landscape were selected to sampling of soils and sediments. These samples were analyzed as for their granulometrical, mineralogical, chemical and chronological characteristics. The results revealed a landscape dominated by sandy to silty soils constituted essentially of quartz and kaolinit, besides muscovite, goethite, sillimanite and albite in low amounts. The high values of SiO2 confirm the quartzic character of these regoliths. The mineralogical and chemical compositions of these materials indicate provenience of metamorphic rocks and of laterites of the area, which due to the dominant warm and humid climatic conditions during the last 1550 years before the present, has been suffering intense chemical weathering and leaching. The landscape evolution is controlled by hidrological erosion of the hillsides and the filling of the valleys of 'veredas' causing the leveling of the landscape and the development of extensive sandy plains from the interfluves soils.